IMPACT OF PHARMACOLOGICAL TREATMENT ON CARDIOVASCULAR AUTONOMIC FUNCTION TESTS IN PATIENTS OF OCD AND ITS CLINICAL RELEVANCE: A FOLLOW-UP STUDY - kaur, Sharanjeet; Sharma, Rajeev; arora, Prinka; Sharma, Arvind (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Obsessive-compulsive disorder (OCD) is associated with increased mortality due to coronary artery disease. Autonomic dysfunction has been associated with an increased risk of developing cardiovascular illness. Thus, this study examined that autonomic dysfunction is inherent in the disease process and it improves with early initiation of treatment. Methods: A total of 50 drug-naive patients meeting the ICD-10 criteria for OCD were subjected to autonomic function tests at baseline and then follow-up assessments were done at the 3rd and 6th month of treatment. The follow-up parameters were compared statistically with the baseline parameters. Results: Difference of time domain parameters of heart rate variability at baseline and second follow-up were statistically significant (p<0.05). Difference of frequency domain parameters of HRV at baseline and second follow-up were also statistically significant (p=0.000). Conclusion: OCD is characterized by inherent autonomic dysfunction. Thus, physicians should carefully monitor metabolic and cardiovascular health in patients with OCD early in the course of the disorder and early initiation of treatment can further prevent these cardiovascular events.